Nutrition and Crohn's Disease: An Overview - C Ó'Moráin (Canadian Journal of Gastroenterology)
Malnutrition is common in Crohn's disease. Nutrition can be improved in patients with Crohn's disease by total parenteral nutrition (TPN) or enteral nutrition. TPN induces long term remission in over 50% of patients with Crohn's disease. Enteral nutrition is as effective, more economical and less hazardous than TPN. Enteral nutrition can be given as a polymeric or elemental diet. Polymeric diets can be helpful by improving patient nutritional and clinical status. Elemental diets have other advantages in that clinical improvement is not only symptomatic. A controlled trial suggests it to be more effective than polymeric diets in acute Crohn's disease. Four controlled studies have shown elemental diets to be as effective as steroids in acute Crohn's disease. How an elemental diet achieves this result is conjectural, but it is unlikely that its action is solely nutritional, as the patient improves before nutritional parameters improve. Elemental diets contain glutamine and arginine, which have a direct effect on intestinal mucosa and improve immune function. Patients with active Crohn's disease have increased intestinal permeability; treatment with an elemental diet improves the permeability defect.